Pengaruh Harga, Kualitas Produk dan Promosi Terhadap Keputusan Pembelian Produk Sepatu Converse Pada Toko Babee.Shopp Padang - Doni Marlius; Kesy Noveliza (EKOMA : Jurnal Ekonomi, Manajemen, Akuntansi, 2022)
This study aims to analyze the effect of price, product quality, and promotion on purchasing decisions for Converse shoes at the babee.shopp Padang store. The data used in this study were collected from consumers who use Converse shoes products at the Babee.shopp Padang store with the accidental sampling method in sample selection. There are 83 samples of consumers who used Converse shoe products at the babee.shopp Padang store. Data analysis used multiple linear regression method. The results showed that the price had no positive and significant effect on purchasing decisions with t-count value (0.486) greater than t-tabel (0.2159), but a significant value greater than 0.05. Product quality has no positive and significant effect on purchasing decisions with t-count value (1.368) greater than t-tabel (0.2159), but a significant value greater than 0.05. While promotion has a positive and significant effect on purchasing decisions for Converse shoes at the babee.shopp Padang store with a t-count value (3.698) greater than t-tabel (0.2159) and a significant value less than 0.05.